ANALISIS EKONOMI LIDAH BUAYA DI TANI ORGANIK MERAPI (TOM) YOGYAKARTA - Wibowo, Hendri; Hastuti, Dewi; Prabowo, Rossi (Universitas Medan Area, 2024)
The existence of various processed aloe vera products produced from agro-industrial activities in CV. Merapi Organic Farmers D.I Yogyakarta who are able to provide processed products for their raw materials in the form of aloe vera cultivation. This study aims to analyze the feasibility of aloe vera farming, as well as factors that influence the decision of business actors in developing aloe vera agribusiness in Merapi Organic Farming. The analysis methods used include farming feasibility analysis, and multiple liner regression. The research was carried out in May-July 2023, using the survey method. The determination of respondents by purposive sampling is farmers in Merapi Organic Farmers. The results of the research showed that the R/C ratio of aloe vera farming had a value of 2.64 using land owned by CV. Merapi Organic Farmers, so that aloe vera farming activities in CV. Merapi Organic Farmers in Yogyakarta are declared feasible based on the calculation of the R/C ratio. Factors that affect farmers' decision-making are the variables of monthly money needs, distance variables, experience variables, and age variables. Aloe vera farmers in CV. Merapi Organic Farmers. It is hoped that farmers will obtain their own seeds, this is in order to minimize large expenses for aloe vera seeds.